Efektifitas Pembelajaran PAI dalam Mencegah Prilaku Pornografi Remaja di SMA "Pohon Mangga" - Renata Cahya Ningrum; Budi Haryanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the intensity of pornographic behavior among students, examine the effectiveness of Al-Islam learning in preventing pornographic behavior, and analyze relevant elements in efforts to prevent pornographic behavior through Al-Islam learning. This study used a descriptive qualitative approach. Data collection techniques included observation, interviews, and documentation. The data obtained were analyzed using interactive data analysis techniques according to Miles, Huberman, and Saldaña, which include data condensation, data presentation, drawing conclusions, and verification. The results indicate that pornographic behavior is present among students at "Pohon Mangga" High School with varying levels of intensity, ranging from mild to severe. The findings also indicate that students in remote areas have relatively broad and fast access to and visit pornographic websites. This indicates the need to strengthen Al-Islam learning in a more contextual and preventative manner to protect students from the negative influence of pornography in the digital age.